A temporal assessment of anthropogenic marine debris on sandy beaches from Ecuador’s southern coast - Salazar, Juliana A.; González, Roger; Navarrete, Alba L.; Calle, Paola; Alava, Juan José; Domínguez, Gustavo A. (Frontiers in Marine Science, 2022)
Anthropogenic marine debris (AMD) is an environmental pollution that affects marine life, human health, wellbeing, and the economy. This marine litter can deposit in the coastlines, particularly on tidal zones and beaches. To pursue mitigation strategies to reduce AMD is important to monitor the amount, type and frequency of litter being dumped on shores. This study presents the composition, temporal distribution, abundance and size of AMD on three sandy beaches from Guayas province, Ecuador. The field data was recollected from December 2018 to February 2020. A total of 12,362 items of AMD were collected with an abundance of 1.95 macro-litter items/m2. The composition of AMD was marked by the predominance of plastic items (91.8 %), followed by wood and cloth (1.9 %), while cigarettes were only present in touristic beaches. Our results suggest that the sites with more AMD abundance are the touristic beaches that are nearby small coastal villages and fishing communities. Also, the AMD abundance is slightly higher at the beginning of the dry season than in the rainy season. Our findings indicate that, it is necessary to implement concerted solid waste management measures and proactive environmental education programs to empower the local population, as well as investigate the anthropogenic sources and other variables influencing the AMD abundance coming onto sandy shores.